(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
Employee engagement has become one of a hot topic in human resource management among the global workforce. The practitioners and academicians identified that employee engagement have a positive impact on individual and organization performance by adoption various scaling technique. The purpose of this research is to bring out the general discussion about the various measurements scaling adopted by researchers to measure employee engagement which is published in various reputed academic journals. The study discussed six measurement scales used by many researchers, and identified the scale which is widely used.